CFOs as Innovators in Debt Maturity Choices: New Evidence from an Asian Emerging Market - Uyen To Diep (Emerging Science Journal, 2026)
This study aims to examine the role of the Chief Financial Officer (CFO) as an agent of innovation in shaping corporate debt maturity decisions within the framework of Upper Echelons Theory. Data were collected from 312 non-financial firms listed in Vietnam from 2011 to 2023, spanning 10 sectors, with focused analysis on three sectors - Industrials, Materials, and Consumer Staples - to highlight their specific characteristics. The personal traits of CFOs, including gender, age, education, and expertise, were analyzed in relation to debt maturity structures, measured by the long-term debt ratio (LTDR) and weighted average debt maturity (WAM). To explore these relationships, various regression methods - OLS, FEM, REM, FGLS, and GMM - were applied. The results reveal that CFO attributes significantly affect debt maturity choices, emphasising their innovative role in corporate financial management. Moreover, this influence varies among sectors: Industrials, Materials, and Consumer Staples exhibit notable differences from other sectors. The study advances the literature by emphasising the pivotal role of CFOs in financial innovation and by extending Upper Echelons Theory. Empirically, it provides novel evidence from an emerging market context, a setting that remains underexplored. Practically, the findings offer insights for firms and investors in selecting and developing CFOs as strategic resources to enhance adaptability and financial stability.